Chemical Priming of Plants Against Multiple Abiotic Stresses: Mission Possible?. (April 2016) - Savvides, Andreas; Ali, Shawkat; Tester, Mark; Fotopoulos, Vasileios
Abstract : Crop plants are subjected to multiple abiotic stresses during their lifespan that greatly reduce productivity and threaten global food security. Recent research suggests that plants can be primed by chemical compounds to better tolerate different abiotic stresses. Chemical priming is a promising field in plant stress physiology and crop stress management. We review here promising chemical agents such as sodium nitroprusside, hydrogen peroxide, sodium hydrosulfide, melatonin, and polyamines that can potentially confer enhanced tolerance when plants are exposed to multiple abiotic stresses. The challenges and opportunities of chemical priming are addressed, with the aim to boost future research towards effective application in crop stress management. Trends: Plant priming using chemical agents such as sodium nitroprusside, hydrogen peroxide, sodium hydrosulfide, melatonin, and polyamines enhances plant tolerance to different abiotic stresses, improving cellular homeostasis and plant growth under stress conditions. Commonly employed chemical priming agents share components in their modes of action. When used against different abiotic stresses, the modes of action of a chemical agent show similarities but also distinct specificities. Chemical priming through using selected chemical agents is a promising tool against various individual or combined abiotic stresses. The efficiency of chemical priming depends highly on the mode of application.